Betaine Treatment Prevents TNF-α-Mediated Muscle Atrophy by Restoring Total Protein Synthesis Rate and Morphology in Cultured Myotubes. (April 2023) - Di Credico, Andrea; Gaggi, Giulia; Izzicupo, Pascal; Vitucci, Daniela; Buono, Pasqualina; Di Baldassarre, Angela; Ghinassi, Barbara
Skeletal muscle atrophy is represented by a dramatic decrease in muscle mass, and it is related to a lower life expectancy. Among the different causes, chronic inflammation and cancer promote protein loss through the effect of inflammatory cytokines, leading to muscle shrinkage. Thus, the availability of safe methods to counteract inflammation-derived atrophy is of high interest. Betaine is a methyl derivate of glycine and it is an important methyl group donor in transmethylation. Recently, some studies found that betaine could promote muscle growth, and it is also involved in anti-inflammatory mechanisms. Our hypothesis was that betaine would be able to prevent tumor necrosis factor-α (TNF-α)-mediated muscle atrophy in vitro. We treated differentiated C2C12 myotubes for 72 hr with either TNF-α, betaine, or a combination of them. After the treatment, we analyzed total protein synthesis, gene expression, and myotube morphology. Betaine treatment blunted the decrease in muscle protein synthesis rate exerted by TNF-α, and upregulated Mhy1 gene expression in both control and myotube treated with TNF-α. In addition, morphological analysis revealed that myotubes treated with both betaine and TNF-α did not show morphological features of TNF-α-mediated atrophy. We demonstrated that in vitro betaine supplementation counteracts the muscle atrophy led by inflammatory cytokines.